A case report of an unusual cause of mitral stenosis in a young woman. Issue 4 (30th October 2018) - Senesael, Ellie; Plein, Danièle; La Meir, Mark; Droogmans, Steven
Abstract: Background: Systemic lupus erythematosus (SLE) is an autoimmune disease, frequently associated with cardiovascular involvement. One of the most frequent complication is mitral valve regurgitation in more than one-third of the patients. Case summary: A 30-year-old woman with arthralgia, butterfly rash, and Raynaud phenomenon presented with a systolic murmur and renal impairment. Based on the kidney biopsy the diagnosis of SLE was made. Echocardiography revealed the presence of pulmonary hypertension, restrictive mitral valve disease with nodular thickening of the anterior leaflet and moderate regurgitation, compatible with Libman Sacks (LS) endocarditis. Immunosuppressive therapy was started and the patient status improved with normalization of systolic pulmonary artery pressure. After 8 years without follow-up, she presented with fatigue and dyspnoea based on a severe mitral valve stenosis. Subsequently, she underwent a minimal invasive mitral valve replacement and the diagnosis of LS endocarditis could be confirmed upon histopathological examination. Discussion: This case demonstrates that LS endocarditis can not only lead to mitral regurgitation but occasionally to mitral stenosis due to chronic inflammation with thickening and fusion of mitral valve leaflets. Hereby, comprehensive echocardiography, inclusive stress echocardiography, plays a critical role.